THE DIDACTIC POSSIBILITIES OF EDUCATING YOUNG PEOPLE TO FRIENDSHIP IN THE FOLK PEDAGOGY OF KARAKALPAK (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In this article, we will describe the didactic possibilities of educating young people to friendship in Karakalpak folk pedagogy, and we will also provide information on its place in pedagogy.